KOMUNIKASI TERAPEUTIK PERAWAT DALAM PROSES PENYEMBUHAN PASIEN PSIKOSIS DI UPT. BINA LARAS PROVINSI RIAU - Gina Oktaria; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research entitled "Therapeutic Communication Nurse In The Process Of Psychosis Patient Healing at UPT. Bina Laras Riau Province ". Psychosis is a mental form characterized by the absence of organizing and personal integration. Therapeutic communication is a planned communication conscious, purposeful and focused activity for the cure of psychosis sufferers. Phase and Technique of therapeutic communication is a way to foster a therapeutic relationship where there is information delivery and the exchange of messages and thoughts with the intention to influence others. Therapeutic communication is not a work that can be ruled out, but must be planned, intentional, and professional action. As appropriate, therapeutic communication nurses give priority to assisting clients, verbalizing feelings and knowing the patient's both verbal and nonverbal responses. The ability of therapeutic communication can not be separated from the behavior of a person that involves physical activity, mental, social background, experience, age, education and goals to be achieved From this research is to explain and describe how the process of communication therapy implemented by nurses Healing psychosis patients in UPT. Bina Laras Riau Province.This research method using descriptive qualitative research method by using obsevation technique, interview and documentation. Research subject is First, Head of UPT. Bina Laras Riau Province, secondly, Social Worker (Pramurukti) nurse is related person in research process that is in taking data about therapeutic communication of a nurse. Data analysis was obtained using Miles and Huberman methods, and the validity of the data itself was tested using Triangulation. Results and conclusions are 1. Therapeutic communication has a big role in the recovery process, especially psychosis patients. This is evident from the results of observations of researchers on the condition of patients who have undergone therapeutic communication within a certain time. The success of therapeutic communication in the recovery process of psychotic patients can not be separatedfrom the implementation of good therapeutic communication stages. There are four stages in therapeutic communication performed by the nurses in the recovery process of psychosis patients: the pre-interaction stage as the preparatory stage before communicating with the patient, the introductory stage to get the attention and trust from the patient, the working stage that is useful to change the patient's behavior for the better And normal, as well as the termination stage in which the nurse decides to complete the meeting on a temporary basis to meet again at another time that has been promised together or forever because the patient has been recovered / normalized.2. In conducting the healing process for psychosis patients, besides using the stages also uses therapeutic communication techniques, there are twenty therapeutic communication techniques such as listening, pointing reception, asking related questions and open questions useful for listening and receiving which the nurse tells the patient by giving Easy to understand questions of the patient as well as useful for knowing the patient's condition through communication by giving the patient a chance to explain his condition and ask related questions. Repeating the patient's speech by using his own words, clarifying, focusing on the purpose for the nurse to provide feedback that he / she understands the patient's message and hopes the communication is continued to equate the nurse's understanding to the patient and to limit the conversation so that the conversation becomes more specific and understood by the patient. The observation aims to make the patient communicate more clearly without the nurse having to ask the patient the way the nurse gives the direction of the conversation. Offer information by giving counseling and socialization to the patient and being silent is used when the patient needs to express the idea but does not know how to do or deliver it. Summarizing aims to repeat the topic of lessons discussed with patients and to reward patients about hygiene such as brushing your teeth diligently and properly will be rewarded. Offered bertujun to nurses provide themselves without response conditional or expected response, provides an opportunity for patients to begin talks with the aim of providing an opportunity for clients to take the initiative in choosing the subject, advocating to continue talks with tujan this technique also indicated that nurses follow what talked about and interested in what will be discussed in a sequence of events with less selanjutnya.Menempatkan sort destination events on a regular basis will help nurses and patients to see it in perspective. Provide an opportunity for the patient to describe the perception, reflection, assertive with the aim to express their opinions, make decisions, and thinking of himself. Humor that aims to reduce stress and pain due to stress and improve the success of nursing care.3. Process the message occurrence of a therapeutic communication between nurses and patients at the start of the delivery of the message by the communicator to the communicant to use the media or not. So it can be concluded that the messages in use are positive, in accordance with the patient's condition.Keywords: Therapeutic Communication, Psychosis